Pengaruh Inflasi, Kurs Rupiah dan Suku Bunga Terhadap Indeks Harga Saham Gabungan Dimoderasi Harga Emas - Noviana Azhar Azizah; Ratnaningrum Ratnaningrum (Ikatan Da'i Indonesia, 2026)
This study aims to analyze the effect of inflation, exchange rate, and interest rate on the Indonesia Composite Index (IHSG) with gold prices as a moderating variable. The data used in this study are monthly time series data from January 2021 to December 2025, analyzed using multiple linear regression and Moderated Regression Analysis (MRA). The results show that inflation has a positive and significant effect on IHSG, while the exchange rate has no significant effect. Interest rates are found to have a negative and significant effect on IHSG. Gold prices strengthen the relationship between inflation and IHSG, but weaken the relationship between exchange rates and IHSG. However, gold prices are not able to moderate the effect of interest rates on IHSG. These findings indicate that the role of gold as a moderating variable is contextual and more effective under conditions of economic uncertainty caused by inflation and exchange rate fluctuations rather than monetary policy changes. This study contributes to the literature by highlighting the role of gold as a safe haven asset in influencing the relationship between macroeconomic variables and stock market performance. This study highlights the contextual role of gold as a moderating variable in emerging stock markets.